Safety, effectiveness and comparability of professional skin cleansers - Sonsmann, Flora Karla; Bock, Meike; Fartasch, Manigé; Gabard, Bernard; Elsner, Peter; Kleesz, Peter; Landeck, Lilla; Pohrt, Ute; Seyfarth, Florian; Schliemann, Sibylle; Diepgen, Thomas L.; Zagrodnik, Fred; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2010)
Background: There are no widely-accepted methodical specifications with which to objectify cleansing effectiveness and skin compatibility of occuptional skin cleansing products in Europe. Therefore the German Social Insurance Agency (DGUV) initiated a study with the goal to evaluate such products in view of the potency and the safety of hand cleansers. A market analysis was a part of the project. Methodology: The product descriptions and safety data sheets of 120 products (5-20/manufacturer) of 11 manufacturers were evaluated between 02/2008 and 04/2008. Results: The manufacturers used mainly ingredients of low irritancy. The declaration of the applied ingredients was in the majority of the cases correctly labeled according to the INCI Declaration. Although there was documentation of skin tolerability for most products, the manufacturers used widely differing tests of skin compatibility. Evidences for cleansing effectiveness were not declared or have not been provided. One manufacturer even promised medical effects of its products. There was no uniform general classification of products making it difficult to identify characteristics of cleansers and choose between them. Conclusions: Presently, there are no commonly accepted criteria to classify products in view of cleansing effectiveness und skin compatibility. Generally accepted criteria and test methods are needed for the evaluation of hand cleansers in order to provide the possibility of transparency and comparability.